The Prevalence of Child Vulnerability and Its Nature: An Analytical Study on Bangladesh Perspective - Md. Abu Shahen (CV. Literasi Indonesia, 2021)
Child vulnerability refers to the conditions where children have not the ability to protect themselves from harassment, maltreatment, and malnutrition which could weaken. This study has tried to reveal the prevalence and the nature of child vulnerability in Bangladesh, and the root causes of child vulnerability have also been explored and debated and discussed throughout the article. However, the study is narrative and qualitative in the manner and secondary data have been used to develop and support the arguments for the study. As findings, the study has also found that children are at great risks due to some notable reasons, such as excessive academic pressure, the worst form of child labor in the working place, disability, child trafficking, and natural disasters which led them to be victimized with maltreatment and malnutrition which is more prevalent in the rural and urban slum areas. Moreover, climate change and disasters have been playing an adverse role to increase the prevalence of children's vulnerability in Bangladesh. In conclusion, the study suggests that decision-makers and policymakers need to be more conscious and responsible to revise the existing legal frameworks and their effective implementation for the protection of children against vulnerability.